The Role of Perceived Value and E-Service Quality of E-Commerce Users to Build Electronic Word Of Mouth (E-WOM) - Pratama, Cikal Virgiawan; Sya’roni, Deden Abdul Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In this digital era, especially after the pandemic, many business people choose to focus on marketing and promoting through various kinds of online media which makes consumers have high flexibility to choose the product they want.. The electronic perceived value in question is to build good values and benefits attached to the product being sold. Another factor that can build Electronic Word Of Mouth is E-Service Quality, with better quality of online service, consumers will not hesitate to promote products on marketplace platform. This study aims to determine the role of Perceived Value on Electronic Word Of Mouth by making 50 Marketplace customers as research samples with is purpossive sampling technique. Instrument for this research using perceived value, e – service quality and electronic word of mouth questionnaire form and also conducted interviews with some respondents after the author first made observations regarding the variables studied. The results of this study indicate that perceived value and e-service quality have a significant effect on electronic word of mouth based on statistical calculations using linear regression analysis, correlation coefficient and partial hypothesis testing. This is due to several factors including product quality management, speed of response from sellers and overall customer satisfaction that builds positive word of mouth